Neurobrucellosis presenting as an intra-medullary spinal cord abscess - Patil Chidanand S; Nagmoti Mahantesh B; Vajramani Girish V (BMC, 2005)
Abstract Background Of the diverse presentation of neurobrucellosis, intra-medullary spinal cord abscess is extremely rare. Only four other cases have been reported so far. We present a case of spinal cord intra-medullary abscess due to Brucella melitensis. Case presentation A forty-year-old female presented with progressive weakness of both lower limb with urinary incontinence of 6 months duration. She was febrile. Neurological examination revealed flaccid areflexic paraplegia with T10 below sensory impairment including perianal region. An intramedullary mass was diagnosed on Magnetic Resonance Image (MRI) scan extending from T12 to L2. At surgery, a large abscess was encountered at the conus medullaris, from which Brucella melitensis was grown on culture. She was started on streptomycin and doxycycline for 1 month, followed by rifampicin and doxycycline for 1 month. At 2-year follow-up, she had recovered only partially and continued to have impaired bladder function. Conclusion Neurobrucellosis, if not treated early, can result in severe neurological morbidity and sequale, which may be irreversible. Hence it is important to consider the possibility of neurobrucellosis in endemic region and treat aggressively.